ESTIMATION OF POPULATION NUMBER VIA LIGHT ACTIVITIES ON NIGHT-TIME SATELLITE IMAGES - M. K. Turan; E. Yücer; E. Sehirli; İ. R. Karaş (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences, 2017)
Estimation and accurate assessment regarding population gets harder and harder day by day due to growth of world population in a fast manner. Estimating tendencies to settlements in cities and countries, socio-cultural development and population numbers is quite difficult. In addition to them, selection and analysis of parameters such as time, work-force and cost seems like another difficult issue. In this study, population number is guessed by evaluating light activities in İstanbul via night-time images of Turkey. By evaluating light activities between 2000 and 2010, average population per pixel is obtained. Hence, it is used to estimate population numbers in 2011, 2012 and 2013. Mean errors are concluded as 4.14 % for 2011, 3.74 % for 2012 and 3.04 % for 2013 separately. As a result of developed thresholding method, mean error is concluded as 3.64 % to estimate population number in İstanbul for next three years.